2011
DOI: 10.1029/2011rs004686
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic wave propagation in inhomogeneous, moving media: A general solution of the problem

Abstract: [1] The exact computation, the exact modeling of the propagation of electromagnetic signals through inhomogeneous moving media, is an old theoretical and measuring/data interpretation problem, because in a lot of practical problems, such as the accurate space-time determination in satellite positioning systems, the occultation measurements, or the accurate tracking of the interplanetary probes, the electromagnetic wave (signal) traverses moving, inhomogeneous media, where the moving velocity of the media and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…A whistler signal consists of a wide range of frequencies. Ferencz et al [2001] found a new solution using the Method of Inhomogeneous Basic Modes [ Ferencz , 1978]. This solution delivers not only the standard electron whistler solution, but the proton and ion whistler solution, the Faraday rotation (TiPP events in the case of f > f p ) and the solution for oblique propagation, also in the case of lossy plasmas.…”
Section: New Inversion Methodsmentioning
confidence: 99%
“…A whistler signal consists of a wide range of frequencies. Ferencz et al [2001] found a new solution using the Method of Inhomogeneous Basic Modes [ Ferencz , 1978]. This solution delivers not only the standard electron whistler solution, but the proton and ion whistler solution, the Faraday rotation (TiPP events in the case of f > f p ) and the solution for oblique propagation, also in the case of lossy plasmas.…”
Section: New Inversion Methodsmentioning
confidence: 99%
“…Because only the resultant of the modes, i.e., the resultant in is the solution of Maxwell's equations we have some degree of freedom choosing from basic modes. (More about this can be seen in [ Ferencz , 2011] or in earlier publications of the MIBM.) The structure of and the fact that A m ′ m , A n n ′ are non‐degenerative in every case suggest that the “basic modes” will be the solutions of the parts of , in which the {…} brackets are present.…”
Section: The Full‐wave Solution Of Maxwell's Equationsmentioning
confidence: 96%
“…Let us search the solution of Maxwell's equations as a sum of “basic modes” in every point, i.e. Fmn=i=1NiFmnorFmn=i=1NiFmnetc. where the index i is the marker of independent basic modes, i = 1, … N and N is the number of the modes in a given point, and we use in the case of index i the normal summation formalism as in the work of Ferencz [2011] too. With this choice Maxwell's equations are i=1N[{0.12emiFmnxa+0.12emiFnaxm+0.12emiFamxn}AmmAnnAaa+iFmn(AmmxaAnn+AnnxaAmm)Aaa+0.12emiFna(AnnxmAaa+Aaaxm...…”
Section: The Full‐wave Solution Of Maxwell's Equationsmentioning
confidence: 99%
See 2 more Smart Citations